Grounds for Appeal: Maasai Customary Claims and Conflicts - Galaty, John G. (Anthropologica, 2022)
In a 1994 episode, Maasai herders from Ewuaso were prevented from watering livestock at wells along the border between two group ranches, but, before strife escalated, the police established control. After such events, talk puts a "local construction" on the event, framing, highlighting, justifying and reinterpreting it to certain aims and purposes. This article discusses the backdrop to conflict in Ewuaso: the subdivision and privatization of group lands, competition for land by political factions and age-sets, claims by the locally powerful and the high Kenyan politics of grabbing land and forging electoral alliances, as global forces appear as local faces.